Technology-mediated intervention and cognitive functioning: a systematic review and meta-analysis (Journal of Statistics on Health Decision, 2022)
There are several types of physical activity activities that are mediated by technology, including sports (8-10) or dancing (11-14). These activities are believed to require both physical and cognitive abilities and have been used to improve physical and cognitive functions in older adults (15-17). To our knowledge there is no systematic review that aimed at synthetizing and evaluating existing evidence on the impact of technology-mediated physical activity on cognitive functioning of older adults with clinical conditions, therefore this study aims to assess the impact of technology-mediated physical activity on the cognitive function of older adults with clinical conditions. A meta-analysis was performed using R packages meta and metafor in RStudio Version 1.4.1103 (Rstudio Team, 2020) running R version 4.0.5 (R Core Team, 2021). Cognitive function was classified into five domains, (1) general cognition (2) immediate verbal memory, (3) delayed verbal memory, (4) attention, and (5) inhibition. Thirteen studies were included in this systematic review (10, 15, 21-31). Results suggest no difference between interventions mediated by technology and the other interventions (i.e. physical exercise and combined physical and cognitive exercise) on the cognition of older adults with clinical conditions. Given the potential benefits of interventions mediated by technology, more research is needed to establish the effective components for cognition and physical function and apply this understanding to the development of evidence-based interventions and stablished guidelines for the best prevention or treatment of cognitive decline.